Preparation and Evaluation of Doxorubicin-Loaded PLA–PEG–FA Copolymer Containing Superparamagnetic Iron Oxide Nanoparticles (SPIONs) for Cancer Treatment: Combination Therapy with Hyperthermia and Chemotherapy - Khaledian M (Dove Medical Press, 2020)
Mohammad Khaledian,1 Mohammad Sadegh Nourbakhsh,1,2 Reza Saber,3 Hadi Hashemzadeh,4 Mohammad Hasan Darvishi5 1Department of Biomedical Engineering, Faculty of New Sciences and Technologies, Semnan University, Semnan, Iran; 2Faculty of Materials and Metallurgical Engineering, Semnan University, Semnan, Iran; 3Research Center for Science and Technology in Medicine, Tehran University of Medical Sciences, Tehran, Iran; 4Department of Nanobiotechnology, Faculty of Bioscience, Tarbiat Modares University, Tehran, Iran; 5Nanobiotechnology Research Center, Baqiyatallah University of Medical Sciences, Tehran, IranCorrespondence: Mohammad Hasan Darvishi Email Darvishi@alumnus.tums.ac.irBackground: Among the novel cancer treatment strategies, combination therapy is a cornerstone of cancer therapy.Materials and Methods: Here, combination therapy with targeted polymer, magnetic hyperthermia and chemotherapy was presented as an effective therapeutic technique. The DOX-loaded PLA–PEG–FA magnetic nanoparticles (nanocarrier) were prepared via a double emulsion method. The nanocarriers were characterized by particle size, zeta potential, morphology, saturation magnetizations and heat generation capacity, and the encapsulation efficiency, drug content and in-vitro drug release for various weight ratios of PLA:DOX. Then, cytotoxicity, cellular uptake and apoptosis level of nanocarrier-treated cells for HeLa and CT26 cells were investigated by MTT assay, flow cytometry, and apoptosis detection kit.Results and Conclusions: The synthesized nanoparticles were spherical in shape, had low aggregation and considerable magnetic properties. Meanwhile, the drug content and encapsulation efficiency of nanoparticles can be achieved by varying the weight ratios of PLA:DOX. The saturation magnetizations of nanocarriers in the maximum applied magnetic field were 59/447 emu/g and 28/224 emu/g, respectively. Heat generation capacity of MNPs and nanocarriers were evaluated in the external AC magnetic field by a hyperthermia device. The highest temperature, 44.2°C, was measured in the nanocarriers suspension at w/w ratio 10:1 (polymer:DOX weight ratio) after exposed to the magnetic field for 60 minutes. The encapsulation efficiency improved with increasing polymer concentration, since the highest DOX encapsulation efficiency was related to the nanocarriers’ suspension at w/w ratio 50:1 (79.6 ± 6.4%). However, the highest DOX loading efficiency was measured in the nanocarriers’ suspension at w/w ratio 10:1 (5.14 ± 0.6%). The uptake efficiency and apoptosis level of nanocarrier-treated cells were higher than those of nanocarriers (folic acid free) and free DOX-treated cells in both cell lines. Therefore, this targeted nanocarrier may offer a promising nanosystem for cancer-combined chemotherapy and hyperthermia.Keywords: combination therapy, doxorubicin, hyperthermia, magnetic nanoparticles, targeted drug delivery